2019
DOI: 10.1021/acs.jmedchem.9b00584
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamide-Based P2X7 Receptor Antagonists Targeting Inflammatory Bowel Disease

Abstract: This report deals with the design, the synthesis and the pharmacological evaluation of pyroglutamide-based P2RX7 antagonists. A dozen were shown to possess improved properties, among which inhibition of YO-PRO-1/TO-PRO-3 uptake and IL1β release upon BzATP activation of the receptor and dampening signs of DSS-induced colitis on mice, in comparison with reference antagonist GSK1370319A. Docking study and biological evaluation of synthesized compounds has highlighted new SAR, and low toxicity profiles of pyroglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…BzATP increased the uptake of TO-PRO-3 in immune cells from both non-tumor and tumor areas ( Figure 2 A-B). This increase was prevented in cells pre-treated with the specific P2RX7 inhibitor, GSK1370319A 35 , indicating that TO-PRO-3 uptake was dependent on the expression of P2RX7. In addition, the macropore activity was delayed in the tumor compartment.…”
Section: Resultsmentioning
confidence: 98%
“…BzATP increased the uptake of TO-PRO-3 in immune cells from both non-tumor and tumor areas ( Figure 2 A-B). This increase was prevented in cells pre-treated with the specific P2RX7 inhibitor, GSK1370319A 35 , indicating that TO-PRO-3 uptake was dependent on the expression of P2RX7. In addition, the macropore activity was delayed in the tumor compartment.…”
Section: Resultsmentioning
confidence: 98%
“…To explore the direct interaction of 2354glu or the selective P2X7 receptor inhibitor, A438079, with P2X7 receptors, we investigated the binding modes using a molecular docking study (Gonzaga et al, ; Homerin et al, ) (Figure S5). We found that all parts of 2354glu were in the P2X7 receptor binding pocket consisting of Lys174, Ile109, Thr111, Glu171, Gln143, Lys145, Lys311, and Val173, while part of A438079 was exposed outside the P2X7 receptor binding pocket.…”
Section: Resultsmentioning
confidence: 99%
“…Despite not having effects on the levels of inflammatory biomarkers, oral administration of AZD9056 induced an overall improvement in the disease symptoms (27). Further investigations are therefore needed to develop P2X7R antagonists that effectively interfere with the inflammatory response; in this regard, several compounds have been proposed and these include Pyroglutamide-Based P2X7R Antagonists (28).…”
Section: P2x Receptor Family Members -P2x7mentioning
confidence: 99%